Analisis Hukum Penyelesaian Sengketa terhadap Pendaftaran Hak Cipta Lukisan yang Memiliki Kesamaan dengan Merek Terdaftar (Studi Putusan Nomor 40/Pdt.Sus-Hak Cipta/2024/PN.Niaga.Jkt.Pst) - Pradipta Nada Damanik; OK Saidin; Jelly Leviza (CV Rewang Rencang, 2025)
Copyright and trademarks can intersect in a single court case in business practice, particularly when a trademark in the form of a painting registered by one party is subsequently registered as copyright by another. This is reflected in the copyright dispute in Decision Number 40/Pdt.Sus- HakCipta/2024/PN.Niaga.Jkt.Pst. This normative juridical research with descriptive-analytical characteristics uses secondary data obtained through library and document studies. The results show that the Copyright Law and Trademark Law provide different forms of protection according to their respective regimes. Article 65 of the Copyright Law reflects legal certainty by providing firm limitations. The judge's legal considerations in the decision were appropriate, providing justice and legal certainty.